The Emergence and Development of Indigenous Tea Plantations in West Java, 1875–1941 (KEMANUSIAAN The Asian Journal of Humanities, 2020)
Indigenous people in Java in the colonial era were often portrayed as a communal society, socially oriented and not in line with the market economy dominated by the Dutch administration. However, this over-simplifies the picture, especially with regard to the late colonial era, when a number of indigenous people voluntarily participated in the market economy, such as in the cultivation of export crops. This article examines the involvement of local farmers in West Java in tea cultivation for export. While this was mediated by their engagement with the colonial government and the European tea estates and infrastructure, the active willingness of local farmers to embrace market economy was also crucial for the emergence of local tea plantations in the region. Throughout the early 20th century until the end of the Dutch colonial era local tea production tended to continuously increase. In addition, several tea enterprises belonging to indigenous people emerged in the region and at least one of them had considerably expanded by the end of the period. This study shows that the indigenous people were actually willing and able to actively participate in the market economy when they had the chance to do so.